Determinants of under-five mortality in Ethiopia using the recent 2019 Ethiopian demographic and health survey data: nested shared frailty survival analysis - Belete Achamyelew Ayele; Sofonyas Abebaw Tiruneh; Melkalem Mamuye Azanaw; Habtamu Shimels Hailemeskel; Yonas Akalu; Asnakew Achaw Ayele (BMC, 2022)
Abstract Background Worldwide, there is remarkable progress in child survival in the past three decades. Ethiopia is off-track on sustainable development targets in under-five mortality since 2020. Therefore, this study aimed to investigate time to death and its associated factors among under-five children in Ethiopia. Methods Nationally representative demographic and health survey data were used for this study. A total of 5772 under-five children were included. Data were analyzed using R software. Semi-parametric nested shared frailty survival analysis was employed to identify factors affecting under-five mortality. Adjusted hazard ratio (AHR) with 95% Confidence interval (CI) was reported and log-likelihood was used for model comparison. Statistical significance was declared at P-value < 0.05. Results The weighted incidence of under-five death before celebrating the first fifth year was 5.76% (95% CI: 5.17 - 6.40). Female sex and under-five children living in urban areas were high probability of survival than their counterparts. After controlling cluster and region level frailty, multiple births (AHR = 7.03, 95% CI: 4.40-11.24), breastfed within one hour after birth (AHR = 0.41, 95% CI: 0.28-0.61), preceding birth interval 18-23 months (AHR = 1.62, 95% CI: 1.12 -2.36), and under-five children younger than 18 months (AHR = 2.73, 95% CI: 1.93 -3.86), and teenage pregnancy (AHR = 1.70, 95% CI: 1.01-2.87) were statistically significant factors for time to under-five death. Conclusion Even though Ethiopia has a significant decline under-five death, still a significant number of under-five children were dying. Early initiation of breastfeeding, preceding birth interval and teenage pregnancy were the preventable factors of under-five mortality. To curve and achieve the SDG targets regarding under-five mortality in Ethiopia, policymakers and health planners should give prior attention to preventable factors for under-five mortality.